2019
DOI: 10.7554/elife.42372
|View full text |Cite
|
Sign up to set email alerts
|

TMEM266 is a functional voltage sensor regulated by extracellular Zn2+

Abstract: Voltage-activated ion channels contain S1-S4 domains that sense membrane voltage and control opening of ion-selective pores, a mechanism that is crucial for electrical signaling. Related S1-S4 domains have been identified in voltage-sensitive phosphatases and voltage-activated proton channels, both of which lack associated pore domains. hTMEM266 is a protein of unknown function that is predicted to contain an S1-S4 domain, along with partially structured cytoplasmic termini. Here we show that hTMEM266 forms ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 80 publications
2
16
0
Order By: Relevance
“…LRRC3B and MMP9 have been associated with mechanisms of cellular proliferation, invasion, and cell cycle regulation [ 53 , 54 ], and interestingly, LRRC3B has been shown to inhibit the expression of MMP9 in one study [ 55 ]. TMEM266 produces a functional voltage sensor at synapses in the cerebellum and thus may play important roles of neuronal signaling [ 56 , 57 ] while TENM2 appears to be involved in neuronal growth and migration [ 58 ]. BIN1 has been associated with neurodegenerative diseases [ 59 ] and may be involved in neuronal function [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…LRRC3B and MMP9 have been associated with mechanisms of cellular proliferation, invasion, and cell cycle regulation [ 53 , 54 ], and interestingly, LRRC3B has been shown to inhibit the expression of MMP9 in one study [ 55 ]. TMEM266 produces a functional voltage sensor at synapses in the cerebellum and thus may play important roles of neuronal signaling [ 56 , 57 ] while TENM2 appears to be involved in neuronal growth and migration [ 58 ]. BIN1 has been associated with neurodegenerative diseases [ 59 ] and may be involved in neuronal function [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Voltage-gated proton channels (H V 1) exist in phylogenetically disparate species where they perform even more disparate functions, from calcification in coccolithophores (1) and mediating action potentials in bioluminescent dinoflagellates (2, 3), to numerous functions in various human tissues (4) such as compensating for electron flux in phagocytes (510) and enabling sperm capacitation (11). Identification of the gene (12, 13) revealed that H V 1 has 4 transmembrane helices, S1 to S4, and is homologous to the voltage-sensing domains (VSDs) present in most voltage-gated ion channels, voltage-sensing phosphatases, and TMEM266 (14). Unlike VSDs of other channels that sense voltage and cause a separate pore to open or close, H V 1 itself conducts protons (15), producing a direct readout of its gating state and making it a unique system for studying gating mechanisms.…”
mentioning
confidence: 99%
“…Having a structural organization similar to animal Hvs is not sufficient to predict proton channel activity, as previously shown with HVRP1/TMEM266, a membrane protein closely related to human Hv1 that does not function as a channel 39 41 . So, we expressed the fungal proteins in Xenopus oocyte and performed electrophysiological measurements in excised membrane patches (Fig.…”
Section: Resultsmentioning
confidence: 95%